2020
DOI: 10.1021/acscatal.0c03776
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Lewis Acid and Photoredox-Catalyzed Trifluoromethylative Difunctionalization of Alkenes with Selenium Ylide-Based Trifluoromethylating Reagent

Abstract: Trifluoromethylative difunctionalization of alkenes with a variety of nucleophiles including amine, azide, alcohol, water, and electron-rich arenes using reagent 1 as trifluoromethyl radical source in the presence of a synergistic catalyst including a Lewis acid scandium­(III) trifluoromethanesulfonate (Sc­(OTf)3) and a photoredox catalyst [fac-Ir­(ppy)3] was described. Mechanistic studies showed that the role of Sc­(OTf)3 in the reaction is to activate reagent 1 via Lewis acid–Lewis base interaction to form c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Although highly successful in integrating various functionalities, the incorporation of amino groups in this ORPC process is rare. 8 This is because amines are easily oxidized under photoredox conditions to electrophilic amine radical cations 9 and thereby lose their nucleophilicity under the ORPC process. Strategically, trapping of this carbocation with nitrile reagent followed by hydrolysis, Ritter type amination, would solve the above issue and allow an amino-functionality to be installed onto alkenes under mild conditions.…”
mentioning
confidence: 99%
“…Although highly successful in integrating various functionalities, the incorporation of amino groups in this ORPC process is rare. 8 This is because amines are easily oxidized under photoredox conditions to electrophilic amine radical cations 9 and thereby lose their nucleophilicity under the ORPC process. Strategically, trapping of this carbocation with nitrile reagent followed by hydrolysis, Ritter type amination, would solve the above issue and allow an amino-functionality to be installed onto alkenes under mild conditions.…”
mentioning
confidence: 99%
“…Consequently, Radical anion 2a –• quickly undergoes Se—C cleavage to give trifluoromethyl radical. [ 4 ] Presumptively, Sc(OTf) 3 may play a similar role to activate reagent 1g to generate trifluoromethyl radical. In addition, excess methanol was required to ensure high conversion and typically methanol was used as cosolvent with acetonitrile in a ratio of 1 : 10.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of a photoredox catalyst and a Lewis acid cocatalyst, reagent 2a was enabled to react with alkenes and a variety of nucleophiles to give trifluoromethylative difunctionlized products in good to excellent yields. [ 4 ] Structure‐activity studies showed the installation of the strong electron‐withdrawing nitro group on the selenium ylide skeleton of reagent 2a plays a pivotal role in enhancing its reactivity, since less than 2% conversion was observed when a para ‐ methoxyphenyl substituted selenium ylide 2b was subjected to the identical reaction conditions for the α‐trifluoromethylation reaction of β‐ketoesters. [ 3 ] Moreover, related studies on other sulfonium ylides based electrophilic difluoromethylating, [ 5 ] monomethylating [ 6 ] and pentafluoroethylating reagents [ 7 ] also disclosed that reagents with a strong electron‐withdrawing group exhibit much higher reactivities than those parent ylides in the absence of such a group.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Since Koike & Akita's report of alkoxytrifluoromethylation using Umemoto's reagent in 2012, 71 several reaction manifolds have been published that achieve this transformation using alternative haloalkyl radical precursors. [72][73][74][75] In general, these reactions proceed via the RPC mechanism depicted in Scheme 2, yielding halogenated a-tertiary ethers in moderate to excellent yields. A noteworthy example was disclosed by Masson in 2019, involving a four-component coupling to forge a nitrile-substituted a-tertiary ether in 59% yield.…”
Section: Photochemical Alkene Difunctionalisationmentioning
confidence: 99%